Diagnostic Accuracy of the Roll Over Test (ROT) and Mean Arterial Pressure (MAP) for Early Detection of Preeclampsia in Pregnant Women - Pusparini Dwi Arisanti; Lumastari Ajeng; Rahajeng Siti Nur Rahmawati; Koekoeh Hardjito (Journal Of Nursing Practice, 2026)
Background: Preeclampsia remains a leading cause of maternal mortality. Early identification of pregnant women at risk is essential to prevent severe maternal and fetal complications. While Mean Arterial Pressure (MAP) and the Roll Over Test (ROT) are used for early detection, there is a need to compare their diagnostic performance in low-resource clinical settings to optimize screening protocols. Purpose: This study aimed to determine the sensitivity and specificity of ROT and MAP in screening for preeclampsia among pregnant women. Methods: This diagnostic observational study used a prospective approach involving 46 pregnant women (gestational age >30 weeks at the Puhjarak Community Health Center, Kediri District. Participants were selected using simple random sampling from a population of 52 eligible pregnant women. Screening was conducted using MAP and ROT, and the occurrence of preeclampsia was evaluated at ≥36 weeks of gestation based on clinical diagnosis. Data were analyzed to calculate sensitivity, specificity, and predictive values. Results: The prevalence of preeclampsia in this study was 17.3%. Both MAP and ROT showed a sensitivity of 75%. However, ROT showed higher specificity (94%) compared to MAP (63%). The PPV for ROT (75%) was also higher than for MAP (30%), Conclusion: There The findings suggest that the ROT may have higher specificity than MAP in screening for preeclampsia. However, further studies with larger samples are needed to confirm these findings.